Production, distribution and marketing of independent cinema in the international market - Cristóbal, Manuel (Historia y Comunicación Social, 2014)
The producer participation in cinema is often distorted and therefore unknown figure. The film industry and the film as a commodity goes beyond its definition, and understanding the basics of production, distribution and marketing are absolutely necessary. In this article these three steps of independent film are discussed in the international market.
Keywords: Production; distribution; strategic marketing; independent cinema; democratization.